The impact mechanism of MRLs standards harmonization on China’s tea export trade—evidence from RCEP countries - Wenjun, Miao; Zenghui, Huo; Fuqiao, Chen; Mei, Zhang (Frontiers in Sustainable Food Systems, 2025)
The RCEP countries are key markets for China’s tea exports, and the harmonization of Maximum Residue Limits (MRLs) standards for pesticides between China and these countries significantly impacts China’s tea trade. Building on previous research, this study develops an enhanced MRLs harmonization index and proposes a theoretical hypothesis that the harmonization of MRLs affects tea export prices and quantities by influencing trade costs. By analyzing tea MRL data from 2010 to 2022, the study finds that the harmonization of MRLs standards between China and the RCEP countries has continuously improved. Estimation results from the stochastic frontier gravity model indicate that MRL harmonization significantly enhances tea export efficiency, a conclusion further supported by robustness and endogeneity tests. Heterogeneity analysis reveals that MRLs harmonization has a stronger impact on tea trade with low- and middle-income countries than with high-income countries. Mechanism analysis further demonstrates that reducing MRLs disparities between China and the RCEP countries reduces tea export costs and effectively boosts export volumes. These findings provide theoretical and practical insights for the RCEP countries to enhance tea trade standard harmonization and promote the sustainable development of regional tea trade.